Estudos sobre a resistência ao toxafeno, de carrapatos (Boophilus microplus, Canestrini, 1888), no Rio Grande do Sul - Correa, Outubrino; Gloss, Roberto Mariano (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
Experiments carried out at the Instituto de Pesquisas Veterinarias "Desiderio Finamor", at Porto Alegre, Rio Grande do Sul, Brazil, to study the degree of resistance of ticks to toxaphene dips, gave the following conclusions: